Housing knowledge of final year student teachers at Esikhawini College of Education : implications for the development of housing unit standards - Dlamini, Buyi P. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MConsumerScience)--Stellenbosch University, 2003.